Miniaturized Two-Dimensional Optical Scanner Based on Planar Waveguide and Flexible Printed Circuit Beam Deflectors - Yingshun Xu; Shujing Liu; Suogang Wang (IEEE Photonics Journal)
In this paper, we present a miniaturized two-dimensional (2-D) optical scanner for endoscopic imaging applications. The optical scanner is based on a hybrid actuation, which is composed of a planar waveguide (PWG) beam deflector for the fast axis and an electrothermally actuated flexible printed circuit beam deflector for the slow axis. The PWG beam deflector utilizing a microheater prism array to rapidly modulate the refractive index of three layers of the PWG is based on the thermo-optic effect. Maximum optical deflection angles of 8.6° for the PWG and 12.4° for the FPC beam deflectors are experimentally achieved. A 1.2-Hz 2-D imaging rate is tested. By assembling two beam deflectors together as well as two rod lenses, an optical scanner highlights small outline dimensions and low-drive voltages, which makes it feasible for endoscopic imaging purposes.